ACCIONES DE LA KESTROFANTINA SOBRE MUSCULO ESTRIADO DE MAMIFERO - POZO, EFREN C DEL (Instituto de Salubridad Publica, CD MEXICO, DF, MEX, 1945)
The anterior lobe of the cerebellum in dogs was removed and the animals observed for 2-3 mos The methods of operation were described The first 2 days postoperatively, the animals could hardly walk and 2 or 3 days later the walk was still ataxic, with os
BOL INST ESTUD MED BIOL
Keywords: ACCIONES, KESTROFANTINA, MUSCULO ESTRIADO, MAMIFERO; CIENCIAS DE LA VIDA; BIOLOGIA ANIMAL; MAMIFEROS